Trends in SAVR with biological vs. mechanical valves in middle-aged patients: results from a French large multi-centric survey - Caus, Thierry; Chabry, Yuthiline; Nader, Joseph; Fusellier, Jean François; De Brux, Jean Louis; , for the EpiCard investigators; Achouh, Paul; Baufreton, Christophe; Bezon, Eric; Bouchot, Olivier; Bourguignon, Thierry; Camilleri, Lionel; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background/introduction Currently, despite continued issues with durability ( 1), biological prosthetic valves are increasingly chosen over mechanical valves for surgical aortic valve replacement (SAVR) in adult patients of all ages, at least in Western countries. For younger patients, this choice means assuming the risks associated with a redo SAVR or valve-in-valve procedure. Purpose To assess the use of mechanical vs. biological valve prostheses for SAVR relative to patient's age and implant time in a large population extracted from the French National Database EPICARD. Methods Patients in EPICARD undergoing SAVR from 2007 to 2022 were included from 22 participating public or private centers chosen to represent a balanced representation of centre sizes and geographical discrepancies. Patients with associated pathology of the aorta (aneurysm or dissection) and requiring a vascular aortic prosthesis were excluded. Comparisons were made amongst centers, valve choice, implant date range, and patient age. Results We considered 101,070 valvular heart disease patients and included 72,375 SAVR (mean age 71.4 ± 12.2 years). We observed a mechanical vs. biological prosthesis ratio (MBPR) of 0.14 for the overall population. Before 50 years old (y-o), MBPR was >1.3 (p < 0.001) while patients above 60 years-old received principally biological SAVR (p < 0.0001). Concerning patients between 50 and 60 years-old patients, MPVR was 1.04 (p = 0.03). Patients 50–60 years-old from the first and second study duration quartile (before August 2015) received preferentially mechanical SAVR (p < 0.001). We observed a shift towards more biological SAVR (p < 0.001) for patients from the third and fourth quartile to reach a MBPR at 0.43 during the last years of the series. Incidentally, simultaneous mitral valve replacement were more common in case of mechanical SAVR (p < 0.0001), while associated CABGs were more frequent in case of biological SAVR (p < 0.0001). Conclusion In a large contemporary French patient population, real world practice showed a recent shift towards a lower age-threshold for biological SAVR as compared to what would suggest contemporary guidelines.